2001
DOI: 10.21273/horttech.11.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Factors Affecting Antioxidant Capacity of Blueberries and other Small Fruit

Abstract: It is now widely held that the antioxidants contained in fruit and vegetables can provide protection against certain human degenerative conditions that are associated with oxygen free radical damage. This view is supported by epidemiological, in vitro, and more recently, in vivo evidence. Phenolics (polyphenolics) contribute substantially to the antioxidant complement of many small fruit species whose ripe fruit are red, purple or blue in color. Fruit containing high levels of phenolic antioxidants wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Concerning this issue, Wang et al (2004) and Escriche et al (2014) observed how different heat treatments resulted alterations in phenolic profiles of honeys. However, industrial processing affects the antioxidant activity and the total phenolics of different honey types differently (Howell et al, 2001;Kowalski, 2013;Chaikham & Prangthip, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning this issue, Wang et al (2004) and Escriche et al (2014) observed how different heat treatments resulted alterations in phenolic profiles of honeys. However, industrial processing affects the antioxidant activity and the total phenolics of different honey types differently (Howell et al, 2001;Kowalski, 2013;Chaikham & Prangthip, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These berries are greatly appreciated due to the superior quality and gained immense popularity among the consumers. Among 400–500 species in Vaccinium genus 1 , blueberries contain higher levels of phenolic compounds, which are high in antioxidant activities 3 , 4 . Presence of phenolic components in berry crops and their activities have been studied thoroughly due to the apparent relationship between the phytochemicals present in the plant product, and its association with the prevention of chronic diseases such as cancer, heart, vascular and neurodegenerative diseases 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Freeze thaw cycles were limited to one (thawed from -80°C then aliquoted and frozen at -20°C until use) to ensure maximal preservation of bioactive components ( Lohachoompol et al, 2004 ). Because seasonal weather patterns and location (e.g., bog versus mountain) have been shown to influence the chemical makeup of various botanicals ( Howell et al, 2001 ), all experiments were conducted using extracts prepared from the same extraction batch to eliminate the potential for differences in the chemical properties of the extracts.…”
Section: Methodsmentioning
confidence: 99%